Quality of life outcomes following velopharyngeal insufficiency surgery. (December 2019) - Li, Lilun; Strum, David; Larson, Stephen; Preciado, Diego
Abstract: Objectives: Velopharyngeal insufficiency (VPI) may be due to functional or anatomic causes, and can lead to speech deficits, communication difficulty, and emotional strain on patients and their caregivers. The VPI Effects on Life Outcomes (VELO) instrument quantifies quality of life outcomes in VPI patients both before and after VPI surgery. This study aims to identify pre-operative patient characteristics associated with better post-operative quality of life. Methods: This study is a retrospective chart review of 51 patients who underwent VPI surgery between 2009 and 2018 at a tertiary free-standing children's hospital. A 26-item parent-proxy VELO questionnaire was administered by telephone to parents to assess their child's quality of life post-VPI surgery. Results: Twenty-seven parents responded to the VELO questionnaire. Average post-operative VELO score was significantly higher in non-syndromic patients as compared with syndromic patients. Average post-operative VELO score was not significantly different between patients with and without submucous cleft (SMC) or those with mild to moderate versus severe pre-operative hypernasality. On multivariate analysis, absence of genetic syndrome, lack of submucous cleft, and presence of severe-pre-operative hypernasality were significantly and positively associated with increased post-operative VELO scores. Conclusion: Children who undergo VPI surgery are more likely to have better post-operative quality of life outcomes if their VPI was not associated with a genetic syndrome or submucous cleft. Non-syndromic and non-SMC patients with severe pre-operative hypernasality may benefit significantly from VPI surgery and have improved post-operative quality of life.